Benzalkonium Chloride: A Known Irritant and Novel Allergen. Issue 1 (January 2016) - Wentworth, Ashley B.; Yiannias, James A.; Davis, Mark D.P.; Killian, Jill M.
Abstract : Background: Benzalkonium chloride (BAK), a detergent and preservative found in health care and household products, is an established irritant, yet BAK is seldom considered to cause allergic contact dermatitis. We have, however, observed positive patch test reactions more often than is typically reported. From 2001 through 2005 and 2006 through 2010, BAK was among the top 10 most frequent allergens in our standard series. Objective: The aim of this study was to review the Mayo Clinic experience from 2000 to 2012 with patch testing to BAK. Methods: An electronic patch test database was used to acquire results of patients who underwent patch testing for BAK 0.1% aqueous after it was introduced to the standard series in 2000 until 2012. Previous reports (1998–2000, 2001–2005, 2006–2010) from our institution were also reviewed. Conclusions: Our study showed BAK to be an allergen of increasing importance. From 1998 through 2000, 2001 through 2005, and 2006 through 2010, the rate of allergic patch test results to BAK increased. More than half of the reactions in each period studied were graded as macular erythema, with at least one third of all reactions deemed to be relevant. Irritancy rates were consistently low.